2022
DOI: 10.1029/2021je007045
|View full text |Cite
|
Sign up to set email alerts
|

Rivers and Lakes in Western Arabia Terra: The Fluvial Catchment of the ExoMars 2022 Rover Landing Site

Abstract: Oxia Planum, the landing site for the ExoMars rover mission, is a shallow basin on the southern margin of Chryse Planitia that hosts remnants of fan‐shaped sedimentary deposits associated with the ancient channel system Coogoon Vallis. This indicates runoff from a catchment in Arabia Terra has transported sediment into the landing site. To explore this fluvial system we created a model catchment for Oxia Planum and, using 6 m/pixel ConTeXt camera orbital remote sensing image data, we digitized the fluvial and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 98 publications
(180 reference statements)
1
17
0
Order By: Relevance
“…This region spans nearly 5,000 km along the transition zone between the northern lowlands and the southern highlands. Arabia Terra bears evidence of groundwater activity (Andrews-Hanna et al, 2007, the existence of deltas (Salese et al, 2019), a potential ocean shoreline (Baker et al, 1991;Di Achille & Hynek, 2010;Rodriguez et al, 2016;Webb, 2004), outflow channels (Fawdon et al, 2022;Molina et al, 2017) volcanic activity (Michalski & Bleacher, 2013;Whelley et al, 2021), and vast deposits of hydrated minerals (Bishop et al, 2020;Gou et al, 2014;Loizeau et al, 2010Loizeau et al, , 2012Loizeau et al, , 2015, 2019Noe Dobrea et al, 2011;Wray et al, 2008). In the west, at the location of the potential shoreline, a region of Arabia Terra called Oxia Planum is the selected landing site of the ExoMars 2022 rover due to a variety of fluvial features and hydrated mineral detections (Lakdawalla, 2019;Quantin-Nataf et al, 2021;Vago et al, 2015Vago et al, , 2017.…”
mentioning
confidence: 99%
“…This region spans nearly 5,000 km along the transition zone between the northern lowlands and the southern highlands. Arabia Terra bears evidence of groundwater activity (Andrews-Hanna et al, 2007, the existence of deltas (Salese et al, 2019), a potential ocean shoreline (Baker et al, 1991;Di Achille & Hynek, 2010;Rodriguez et al, 2016;Webb, 2004), outflow channels (Fawdon et al, 2022;Molina et al, 2017) volcanic activity (Michalski & Bleacher, 2013;Whelley et al, 2021), and vast deposits of hydrated minerals (Bishop et al, 2020;Gou et al, 2014;Loizeau et al, 2010Loizeau et al, , 2012Loizeau et al, , 2015, 2019Noe Dobrea et al, 2011;Wray et al, 2008). In the west, at the location of the potential shoreline, a region of Arabia Terra called Oxia Planum is the selected landing site of the ExoMars 2022 rover due to a variety of fluvial features and hydrated mineral detections (Lakdawalla, 2019;Quantin-Nataf et al, 2021;Vago et al, 2015Vago et al, , 2017.…”
mentioning
confidence: 99%
“…Global palaeolake catalogs have so far identified only one open-basin palaeolake in western Arabia Terra (Fassett & Head, 2008b;Goudge et al, 2012), but local studies to the north and south of our study have identified additional examples (Fawdon et al, 2021;Wilson et al, 2016). The seven open-basin palaeolakes in this work are therefore significant in further characterizing the style, distribution, and frequency of lacustrine processes in the region, and add to the broader understanding of lacustrine systems on Mars.…”
Section: Regional Hydrology and Martian Palaeolakesmentioning
confidence: 70%
“…The widespread occurrence of liquid water on ancient Mars is supported by evidence for hundreds of palaeolakes within the Noachian aged (>3.7 Ga) southern highlands (Cabrol & Grin, 1999Fassett & Head, 2008b;Fawdon et al, 2021;Goudge et al, 2012Goudge et al, , 2015Goudge et al, , 2016Goudge et al, , 2021Irwin III et al, 2005). The global characterization and distribution of palaeolakes has helped to constrain past climatic and hydrological conditions on Mars (Kite, 2019;Milliken et al, 2010;Wilson et al, 2016), and to identify possible past habitable environments (Fairén et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although the presence and specific characteristics of any deep aquifer is still an ongoing debate (Sori and Bramson, 2019;Bierson et al, 2021), the possibility of their existence is intriguing due to the protection from solar radiation such depths would provide for microbial life. Regardless, in spite of unequivocal evidence for extant groundwater on Mars are sparse, there are abundant geological clues that point toward a warmer and wetter planet with a complex hydrogeological history (e.g., Carr and Head, 2010;Di Achille and Hynek, 2010;Orofino et al, 2018;Salese et al, 2019;Dickeson and Davis, 2020;Dickeson and Davis, 2020;Fawdon et al, 2022;Michalski et al, 2022;Schmidt et al, 2022).…”
Section: Introductionmentioning
confidence: 99%